2018
DOI: 10.1016/j.gore.2018.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Radical resection of an endometrioid carcinoma arising from endometriosis in the round ligament within the right canal of Nuck: a case report and literature review

Abstract: HighlightsA patient had endometrioid adenocarcinoma arising from endometriosis in the canal of Nuck.The tumor invaded muscles in the inguinal region.She showed favorable prognosis by radical surgery and adjuvant chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…The risk of malignant transformation of endometrial deposit is between 0.7 and 1.0% [ 13 ] with only 6 cases of cancers associated with inguinal endometriosis have been reported in the literature [ 14 , 15 ]. Of those, five out of six were adenocarcinomas, and one was an endometrial stromal sarcoma [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The risk of malignant transformation of endometrial deposit is between 0.7 and 1.0% [ 13 ] with only 6 cases of cancers associated with inguinal endometriosis have been reported in the literature [ 14 , 15 ]. Of those, five out of six were adenocarcinomas, and one was an endometrial stromal sarcoma [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…A total of 20 studies (18 case reports and 2 case series), which comprised 36 patients who were diagnosed with an endometriotic lesion arose in the NC, were finally considered eligible for inclusion in the qualitative analysis of the present systematic review [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…In 27 of them, imaging was suspicious for presence of a cystic structure in the inguinal region which was compatible with pathology in the NC potentially indicative of Nuck hydrocele in most cases, while preoperative suspicion of the presence of endometriosis through imaging was made for 4 patients. Three patients underwent a preoperative histologically-based diagnostic procedure (biopsy or fine needle aspiration-FNA) [ 26 , 32 , 37 ]. In 2 of them, a preoperative percutaneous biopsy of the mass revealed endometrial tissue, while in the other patient, inguinal mass biopsy revealed adenocarcinoma [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations